Proposta de avaliação dos procedimentos de execução de fachadas argamassadas - Dourado, Gustavo Henrique de Oliveira (Universidade Federal de São Carlos, 2020)
The facades are a complex building system and require a multidisciplinary study and can be a source of waste, pathological manifestations, and accidents at work. These problems may be mitigated with detailed knowledge of the service's development and a production project to carry out this phase. In this work, seven procedures will be compared to the external cladding execution service in concrete structural masonry buildings, identified from the bibliography on the subject. The particularities of the execution of the service in three different buildings will be discussed. As support for data collection in the field, an evaluation protocol was developed to identify and discuss mortar facades' execution practices. The results demonstrated a diversity of best practices and relative compliance with the procedures for carrying out this service. The service's conformity was evaluated based on the proposal of a schematic model that allowed comparing and scoring the service concerning the more significant similarity concerning the subject literature. The proposed protocol proved to be simple and easy to be applied, becoming a tool of quality management of this service. Companies must standardize processes and look for alternatives and equipment that guarantee efficiency, productivity, and safety for workers in their respective services.
Proposal for evaluating mortar façade execution procedures
Keywords: Execução de fachadas; Fachadas argamassadas; Planejamento e controle; Construção civil; Façade execution; Mortar façade; Planning and control; Civil construction; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL